Demographic and Epidemiological Transitions in Nepal: Demographic Implications By Juhee Vajracharya Suwal - Kunwar, Laxman Singh (Economic Journal of Development Issues, 2012)
Publisher: New Delhi: ADROIT PUBLISHERS, 2012, xvii+ 253p; Rs. 1272.00 DOI: http://dx.doi.org/10.3126/ejdi.v13i0.7220 Economic Journal of Development Issues Vol.13 & 14 2011, pp.152-154